The "trauma pitch": How stigma emerges for Iraq and Afghanistan veterans seeking disability compensation. - Katinka Hooyer (PLoS ONE)
Posttraumatic Stress Disorder continues to be a highly stigmatized disease for the veteran population and stigma, experienced as a mark of discredit or shame, continues to be identified as the main deterrent in treatment seeking. Little attention has been paid to how the process of obtaining service-connected disability status can amplify veterans' perceptions of being stigmatized. The following ethnographic study identified how combat veterans experienced stigma in processing through Veterans Affairs care and the effects of linking a Posttraumatic Stress Disorder diagnosis with disability compensation. Stigma was identified in two inter-related areas: 1) the structural level in the Veterans Affairs disability claims process and 2) the individual level in interactions with Veterans Affairs service providers. Findings based on veterans' narratives suggest that the disability claims process, requiring multiple repetitions of personal trauma, coupled with perceptions of institutional stigmas of malingering, created bureaugenic effects: a worsening of symptoms caused by bureaucratic protocols intended to help veterans. This process influenced first time treatment users of the Veterans Affairs by deterring treatment-seeking behavior but was not found to affect veterans who had already initiated treatment. Despite the experience of stigma and commodification of their suffering through disability and diagnostic screening, veterans still sought disability compensation. Veterans viewed this compensation as acknowledgment of their loss and validation of their sacrifice.